Therapeutic Role of Selenium in Reversing Arginase Dysfunction Induced by Pesticide Stress in Fish - Malini, Dr. Anshu; Verma, Dr. Rajesh; Kumar, Dr. Dhyanendra (American Journal of Biodiversity, 2025)
Aquatic ecosystems are increasingly threatened by agricultural pollutants, with pesticides like chlorpyrifos exerting toxic effects on non-target aquatic organisms such as fish. One of the lesser-explored consequences of such exposure is the disruption of the urea cycle, particularly the impairment of arginase, a critical enzyme involved in ammonia detoxification. This study investigates the therapeutic potential of selenium in restoring arginase function and reducing oxidative stress in Labeo rohita exposed to chlorpyrifos. Healthy specimens of Labeo rohita were divided into four groups: control, pesticide-exposed, pesticide with selenium supplementation, and selenium-only treatment. Chlorpyrifos exposure (0.05 ppm for 15 days) significantly suppressed hepatic arginase activity and antioxidant enzyme levels (CAT, SOD, GPx), while increasing lipid peroxidation (MDA content), indicating oxidative stress. Selenium supplementation (0.5 mg/kg feed for 15 days) following pesticide exposure significantly reversed these effects, restoring arginase activity to 69.2 ± 2.8 U/mg protein (compared to 42.6 ± 3.2 U/mg in the pesticide group) and reducing MDA levels by more than 50%. Antioxidant enzyme activities also improved substantially, approaching control levels. Comparative analysis with prior studies further validated the efficacy of selenium as a therapeutic agent. The selenium-only group showed no deviation from baseline, confirming its safety at the tested dose. These results underscore the dual protective and restorative role of selenium in aquatic toxicology and its potential application as a dietary supplement in aquaculture, especially in regions affected by pesticide runoff. This study not only contributes to the understanding of enzymatic dysfunction caused by pesticide exposure but also opens new avenues for the nutritional management of fish health in polluted environments.